2020
DOI: 10.3389/feart.2020.00245
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Impacts of Land Use and Land Management on Summer Temperatures

Abstract: Land use has been recognized as an important anthropogenic forcing of climate change in recent studies. However, climatic effects of land management practices have been little discussed and compared to land-use impacts. As land-atmosphere interactions via surface fluxes are particularly strong during the warm season, we investigate the impacts of historical land use and present irrigation practices on summer temperatures in the Northern Hemisphere using the most recent version of Community Earth System Model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…One bias that the models could have is that irrigation quantities, even though realistic at the annual timescale (Thiery et al., 2017), might be applied in different months/seasons than the ones where irrigation is actually happening (Jha et al., 2022). For the air temperature, the annual maximum of monthly air temperature ( T max ) was considered instead, as previous studies have shown more significant irrigation impacts on hot extremes (Chen & Dirmeyer, 2020; Pitman et al., 2012; Thiery et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…One bias that the models could have is that irrigation quantities, even though realistic at the annual timescale (Thiery et al., 2017), might be applied in different months/seasons than the ones where irrigation is actually happening (Jha et al., 2022). For the air temperature, the annual maximum of monthly air temperature ( T max ) was considered instead, as previous studies have shown more significant irrigation impacts on hot extremes (Chen & Dirmeyer, 2020; Pitman et al., 2012; Thiery et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is not usually a “hot spot” of L‐A coupling like the Great Plains of North America or the Sahel region of Africa (Koster et al., 2006). Not only can such areas experience magnified responses to droughts and heat waves, the local climate may also react more strongly to land cover changes, agricultural practices, and climate change (Chen & Dirmeyer, 2020; Dirmeyer et al., 2013). Given the concurrent dry and warm conditions during the summer of 2018, we pose the question: Did northern Europe enter an unprecedented regime of L‐A feedbacks—that is, did it become a coupling “hot spot” that may have intensified the heatwave?…”
Section: Introductionmentioning
confidence: 99%
“…When each period's anomalies and standard deviations for temperature, sensible heat, and potential sensible heat are used for each model, the left panel shows that the multimodel median of the 90th percentile value of π shows a significant consensus change over portions of the globe. Decreases correspond largely to areas of land cover change: areas of agricultural expansion over the Americas, Northeast China, India, the Sahel, and Australia, but the correspondence between land use change and land-heat coupling has not been explicitly quantified in this study as it has been in others (e.g., Chen and Dirmeyer, 2019;Chen and Dirmeyer, 2020;Hu and Sun, 2022). Increases are largely confined to low latitudes, corresponding to areas of tropical deforestation but also in the subtropics of the Southern Hemisphere during austral summer (Figure 2) and, curiously, much of the Sahara.…”
Section: Figurementioning
confidence: 99%